Communication versus problem solving in a single session of behavioral couple therapy. (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The present study explores the usefulness of two alternative interventions in a single session of behavioral couple therapy. Each intervention was applied to three couples. One intervention consisted of increasing the participants awareness of their communication patterns. In the other, a problem-solving model was taught. On separate days, both before and after the intervention, conversations were recorded between the couple, about their target problem. After the awareness intervention, there was an increase in clear questioning, in criticism, and in rejection of proposals made by the other partner. After the problem-solving training, we observed an increase in the number of proposals, interruptions and criticisms of the partner, as well as, for two couples, a decrease in the rejection of the partners proposals. It may be concluded that both interventions affect conversational style. However, a closer analysis of the results suggested that the initial session of couple therapy should preferably promote a full awareness about detrimental patterns of communication, instead of teaching problem-solving strategies.
Keywords: Communication; Problem-solving; Behavioral couple therapy